Evaluasi Kebijakan Pembangunan Terminal di Kota Malang (Studi pada Terminal Hamid Rusdi Kota Malang) - Ruliansyah, Iqbal (Jurnal Ilmiah Administrasi Publik, 2018)
The construction of Hamid Rusdi Terminal was initially one of the efforts of Malang City Government to break up the traffic in Gadang area and its surroundings due to avoid heavy traffic, besides that Gadang Terminal was unable to accommodate vehicles and passengers due to the existence of a gadang market that is integrated with the gadang terminal. The construction of Hamid Rusdi Terminal is seen as one of the solutions, but it is not working well, so the policy should be evaluated. This research uses descriptive qualitative method by focusing on 1) Development Policy Planning Process of Hamid Rusdi Terminal Malang 2) The Impact of Ongoing Development Policy of Hamid Rusdi Terminal 3) Future Challenge for Hamid Rusdi Terminal can run in accordance with policy objectives. The result of the evaluation of Hamid Rusdis terminal development policy shows that at the planning stage the policy does not go through a rigorous planning process. So the construction of Hamid Rusdi Terminal is not in line with expectations.